Answer:
-4
Step-by-step explanation:
4x+3y=-1
3x + y=-7
Solve for Y
3x+y=-7
-3x. -3x
y= -3x - 7
Plug in Y into the top equation
4x + 3 (-3x - 7) = -1
Distribute the Parenthesis
4x -9x-21=-1
Combine Like terms
-5x = 20
Divide by -5 on both sides
20/-5
x = -4
Question isnt well formatted :
Answer:
1 : 6
Step-by-step explanation:
Given the question :
3x = 1/2y
3x = y/2
Multiply both sides by 2
3x * 2 = y/2 * 2
6x = y
This can be interpreted as :
y = 6 times the value of x
x = y/6
x : y
1 : 6
Let us say that:
x = the number of T shirts bought = 4
y = the number of leather jackets bought = 1
a = the price of the T shirts
b = the price of the leather jackets
With the given variables, we can say that the total cost
is:
total cost = a x + b y
Since, b = 6 a, therefore:
total cost = a x + 6 a y
total cost = a (x + 6 y)
Since total cost is 209, therefore we can calculate for a
since x and y are also given:
209 = a (4 + 6 * 1)
209 = a (10)
a = $20.9
<span>Therefore each T shirt cost $20.9</span>
Step-by-step explanation:
In the second step while opening the bracket, instead of 'a', there should be - 4a.
Answer:
g = number of girls;
b= number of boys
we know that: g= 6+2b
and that: g+b= 156 kids in total
so we may write g+b=(6+2b)+b=6+3b
but g+b= 156
so 6+3b = 156 => 3b= 156-6=150 => b=150/3=50 => b = 50 (number of boys)
g= 6+2b= 6+2 x 50= 106 => g =106 (number of girls)
Step-by-step explanation: